Effect of quercetin on muscle growth and antioxidant status of the dark sleeper Odontobutis potamophila - Zhu, Chenxi; Liu, Guoxing; Gu, Xiankun; Yin, Jiawen; Xia, Aijun; Han, Mingming; Zhang, Tongqing; Jiang, Qichen (Frontiers in Genetics, 2022)
Quercetin is a flavanol beneficial in reducing fat, promoting muscle growth, and Anti-oxidation. To study its effects in freshwater fish, the full-length cDNA of the follistatin (FST) and myostatin (MSTN) genes of the dark sleeper Odontobutis potamophila were cloned for the first time. Juvenile individual O. potamophila was exposed to quercetin at one of four concentrations (0, 2.5, 5, and 10 mg/L) for 21 days. The expression level of MSTN which inhibits muscle growth in the quercetin solution was lower than in the unexposed control group. The genes that promote muscle growth are in TGF-β superfamily like FST, TGF-β1 (transforming growth factor-beta 1), and Myogenic regulatory factors (MRFs) like Myf5 (myogenic factor 5), MyoD (myogenic differentiation), MyoG (myogenin), were higher than in the control group. Apolipoprotein and growth hormone receptor transcription levels in the quercetin-treated fish were significantly lower than in the control group. The concentrations of triglyceride, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol in the muscle tissue decreased, and the lipid-lowering function of quercetin was also demonstrated at the biochemical level. In this study, we analyzed the mRNA levels of AKT, Keap1 (kelch-like ECH-associated protein 1), Nrf2 (NF-E2-related factor 2) oxidation-related genes in the Nrf2/ARE antioxidant pathway, and Malondialdehyde (MDA), catalase (CAT) activity and glutathione (GSH) content in the hepatopancreas of O. potamophila after quercetin treatment, the mRNA expression of AKT, Nrf2 and CAT activity and GSH content are higher than in the control group. Quercetin enhances antioxidant properties and positively affects muscle growth. The results showed that quercetin has no significant effects on the growth performance of O. potamophila, but is effective in increasing muscle growth rate and lowering muscle fat content.